극조숙 고품질 내냉성 벼 신품종 ‘한설’ - 이정희(Jeong-Heui Lee); 신영섭(Shin Young-Seop); 정오영(O-Young Jeong); 김명기(Myeong-Ki Kim); 김연규(Yeon-Gyu Kim); 김홍열(Hong-Yeol Kim); 이점호(Jeom-Ho Lee); 이정일(Jeong-Il Lee); 조영찬(Young-Chan Cho); 전용희(Yong-Hee Jeon); 최용환(Yong-Hwan Choi); 양창인(Chang-Ihn Yang); et al. (Korean journal of breeding, 2010)
‘한설’은 1997년 고품질 극조숙 안전 다수성 품종을 육성할 목적으로 양질 극조숙인 ‘진부24호’를 모본으로 초형이 좋고 극조숙 내냉 다수성 계통인 ‘진부25호(운두벼)’를 부본으로 인공교배하여 2009년 육성한 극조숙 고품질 내냉성 벼 품종으로 주요 특성과 수량성을 요약하면 다음과 같다. 1. 출수기는 7월 25일로 ‘진부벼’보다 4일 정도 빠른 극조생종이며, 간장은 65 cm로 ‘진부벼’보다 약간 작고, 주당 이삭수는 12개, 이삭당 벼알수는 99 ‘Hanseol’ is a new very early-maturing, cold tolerant and high quality japonica rice variety developed from a cross of ‘Jinbu24’ and ‘Jinbu25’ by the rice breeding team of National Institute of Crop Science (NICS), Rural Development Administration (RDA) in 2009. The heading date of this variety is July 25, which is four days earlier than check variety, ‘Jinbubyeo’. ‘Hanseol’ has 65 cm of culm length, 99 spikelets per panicle, 82.9% of ripened grain rate, and 21.5 g of 1,000 grain-weight of brown rice. This variety shows susceptibility to bacterial leaf blight and virus diseases, and insect pests. It is tolerant to cold stress in terms of less heading delay and high fertility in cold water irrigated cultivation. This variety shows delayed leaf senescence and considerable tolerance to viviparous germination at ripening stage. The milled rice of this variety exhibits translucent, clear non-glutinous endosperm and medium-short grain. ‘Hanseol’ showed low gelatinization temperature and 6.1% protein content, 19.1% amylose content and good palatability of cooked rice. The milled rice yield of this variety is about 5.43 MT/ha at ordinary culture in local adaptability test for three years. ‘Hanseol’ would be highly adaptable to mid-north and mid-mountainous areas, and mid-northern alpine area in Korea.